Leaf, root, and soil microbiomes of an invasive plant, Ardisia crenata, differ between its native and exotic ranges - Nakamura, Naoto; Toju, Hirokazu; Kitajima, Kaoru (Frontiers in Microbiology, 2023)
Ecological underpinnings of the invasion success of exotic plants may be found in their interactions with microbes, either through the enemy release hypothesis and the enhanced mutualism hypothesis.Whereas recent high-throughput sequencing techniques have significantly expanded our understanding of plant-associated microbiomes and their functional guilds, few studies to date have used these techniques to compare the microbiome associated with invasive plants between their native and exotic ranges. In this study, we extracted fungal and bacterial DNA within leaf endosphere, root endosphere and rhizosphere soil of an invasive plant, Ardisia crenata, sampled from their native range Japan and exotic range Florida, USA. By analyzing an Illumina sequencing data, we compared microbial community compositions and diversity between the native and exotic ranges. Furthermore, we tested whether abundance of pathogenic or mutualistic microbes differ between the native or exotic ranges in accordance to the enemy release hypothesis or the enhanced mutualism hypothesis. Our results revealed different community compositions across all plant parts between the native and exotic ranges for both fungi and bacteria, leading to two key conclusions. Firstly, despite a higher microbial diversity in the rhizosphere soil in the exotic range than in the native range, the microbial diversity within leaf and root was notably lower in the exotic range compared to the native range. This implies a plant control over what microbes out of the locally available species pool in the soil become associated with roots. Secondly, leaves in the native range harbored a greater number of plant pathogenic fungi compared to those in the exotic range. Some of these fungi are known to cause specific disease in A. crenata in its native range, as predicted by the enemy release hypothesis. These findings suggested potential importance of leaf pathogenic fungi in explaining the difference in population dynamics of invasive plants between their native and exotic ranges.